Interplay between information systems and environmental management in ISO 14001-certified companies: Implications for future research on big data - Fiorini, Paula De Camargo; Jabbour, Charbel Jose Chiappetta; Jabbour, Ana Beatriz Lopes de Sousa; Stefanelli, Nelson Oliveira; Fernando, Yudi (Emerald Publishing Limited, 2019)
Purpose: The purpose of this paper is to identify the contributions of information systems (IS) for the evolutionary process of corporate environmental management by highlighting implications for big data research. Design/methodology/approach: The authors conducted two case studies with Brazilian enterprises certified by ISO 14001, by conducting interviews, document analysis and direct observation. Implications for a research agenda on big data are also presented.